2022
DOI: 10.1155/2022/7895246
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Antiovarian Cancer Mechanisms of Salvia Miltiorrhiza Bunge by Network Pharmacological Analysis and Molecular Docking

Abstract: Background. Ovarian cancer was one of the gynecological malignant tumors. Salvia miltiorrhiza Bunge (SMB) was a kind of herbal medicine with an antitumor effect. However, the inhibitory effect of SMB on ovarian cancer and its potential mechanism were still unclear. Objective. The antitumor effect of SMB on ovarian cancer was studied by network pharmacology and molecular docking techniques, and its possible molecular mechanisms were analyzed. Method. The active ingredients of SMB and the target data of ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Molecular dynamics simulations can identify the trajectory of and temporal changes in the complex, as well as discover atomic interactions between ligands and protein amino acid residues, which can validate and complement molecular docking results. For instance, Xu et al found that Salvia miltiorrhiza Bunge could inhibit ovarian cancer via the PI3K-Akt signaling pathway [24]. Using network pharmacology, Hu et al revealed that wolfberries can treat breast cancer by acting on ESR1, MYC, and other targets [25].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics simulations can identify the trajectory of and temporal changes in the complex, as well as discover atomic interactions between ligands and protein amino acid residues, which can validate and complement molecular docking results. For instance, Xu et al found that Salvia miltiorrhiza Bunge could inhibit ovarian cancer via the PI3K-Akt signaling pathway [24]. Using network pharmacology, Hu et al revealed that wolfberries can treat breast cancer by acting on ESR1, MYC, and other targets [25].…”
Section: Introductionmentioning
confidence: 99%